O problema do Paralelismo Psicofisiológico segundo a Epistemologia Genética - Pessoa, Kátia Batista Camelo [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
In this work we analyze how Piaget explains the nature of the relations between the structures of conscious actions and the physiological mechanisms that accompany them, for this is a problem common to many areas of knowledge, specially to Psychology and, more specifically, to Genetic Psychology and Genetic Epistemology. The solution of corresponding the structures of consciousness to the organic structures does not explain the nature of this link, because, with mere correspondence, if consciousness is only the subjective aspect of certain nervous activities, so does not comprehend which one is the function of consciousness. In the case of Parallelism, a psychophysiological correspondence is sought and a principle of psychophysiological isomorphism is invoked. It arises, therefore, a problem to Parallelism, that is show how two parallel structures act one on another. Our main goal with this research is to explain which is the problem put by Piaget and its solution: the hypothesis, proposed by him is that the parallelism between the states of consciousness and the concomitant physiological processes must be understood in terms of a partial isomorphism between the systems for implications in the broad sense and causalitydependent systems. It is necessary to explain how, clarifying the mode of such correspondence occurs, once there is no interaction exactly between the two heterogeneous structures, the of consciousness and the neurophysiological. After all, as Piaget says, consciousness is nothing or it depends on original and specific categories. We seek to show how Piaget comes to a third way of solution: the comprehension of the brain’s operation depends on the causal structures built by scientists, while knowledge-subjects, and represented in abstract models, including scientific theories. In this sense, implication is an original and specific category of conscious processes and the scientists judge the implications which arise...

Nesse trabalho analisamos como Piaget explica a natureza das relações entre as estruturas de ações conscientes e os mecanismos fisiológicos que as acompanham, pois esse é um problema comum a diversas áreas do conhecimento, em especial, à Psicologia e, mais especificamente ainda, à Psicologia Genética e à Epistemologia Genética. A solução em corresponder as estruturas da consciência às estruturas orgânicas não explica a natureza dessa ligação, pois, com a mera correspondência, se a consciência é somente o aspecto subjetivo de certas atividades nervosas, então não se compreende qual é a função da consciência. No caso do paralelismo, busca-se uma correspondência psicofisiológica e um princípio de isomorfismo psicofisiológico é invocado. Surge, então, um problema para o Paralelismo que é o de mostrar como duas estruturas paralelas agem uma sobre a outra. Nosso principal objetivo neste trabalho de pesquisa é o de mostrar qual é o problema colocado por Piaget e sua solução: a hipótese, proposta por ele, é que o paralelismo entre os estados de consciência e os processos fisiológicos concomitantes deve ser entendido em termos de um isomorfismo parcial, entre os sistemas de implicações no sentido amplo e os sistemas dependentes da causalidade. É preciso explicar como, esclarecendo o modo que tal correspondência ocorre, uma vez que não há interação propriamente dita entre as duas estruturas heterogêneas, as de consciência e as neurofisiológicas. Afinal, como diz Piaget, ou a consciência não é nada ou, então, ela depende de categorias originais e específicas. Procuramos mostrar como Piaget chega a uma terceira via de solução: a compreensão do funcionamento do cérebro depende das estruturas causais construídas pelos cientistas, enquanto sujeitos do conhecimento, e representadas nos modelos abstratos, inclusive nas próprias teorias científicas. Nesse sentido, a implicação é uma...
Keywords: Piaget, Jean, 1896-1980; Epistemologia genetica; Educação - Filosofia; Psicologia educacional; Genetic epistemology